La responsabilité professionnelle médicale : pathologie et thérapie - Baudouin, Jean-Louis (Assurances, 1989)
Me Jean-Louis Baudouin, full professor at the Faculty of Law of the University of Montreal, brilliantly exposes two distinct aspects of the problem of medical professional liability: firstly, the spiralling number of suits and the astronomical sums awarded by courts and, secondly, the possible solutions which would improve the present situation. With medical professionals constantly faced with the threat of being sued, the author fears a destabilization of the practise of medicine and believes the legal system can play a key role in striking a perfect balance.